ANALISIS PERBANDINGAN TEORI DAN KONSEP PENDIDIKAN ISLAM DAN BARAT - Mochamad Daffa Akmal; Adesna; Fitrima Suarni; Iswan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the comparative paradigms of Islamic education and Western education from the perspective of philosophy of education, particularly focusing on ontological, epistemological, and axiological dimensions. Islamic education is fundamentally based on a theocentric paradigm that positions revelation as the primary source of knowledge and emphasizes spiritual and moral values as the foundation of the educational process. In contrast, Western education developed from the traditions of rationalism and empiricism, which emphasize the role of human reason and empirical experience as the basis for the development of scientific knowledge. This research employs a qualitative approach using a library research method by examining various scholarly sources discussing the concepts of Islamic and Western education. The findings indicate that Islamic education promotes a holistic orientation that integrates intellectual, spiritual, and moral development. On the other hand, modern Western education primarily focuses on rational development, critical thinking skills, and mastery of science and technology in responding to the dynamics of modern society. These differing paradigms influence not only the educational objectives but also affect curriculum structures, learning methodologies, and pedagogical relationships between teachers and students. Despite these fundamental differences, both educational systems possess the potential to complement each other in developing contemporary educational frameworks. The integration of spiritual and moral values from Islamic education with the scientific approach and pedagogical innovations of Western education may offer an alternative model for building a more comprehensive and holistic educational system capable of addressing global challenges in the modern era.